Low back pain in patients with rheumatoid arthritis: Clinical characteristics and impact of low back pain on functional ability and health related quality of life - Baykara, Rabia Aydogan; Bozgeyik, Zulkif; Akgul, Ozgur; Ozgocmen, Salih (Ios Press, 2013)
OBJECTIVES: The aim of this study was to assess the point prevalence of low back pain (LBP) in patients with rheumatoid arthritis (RA); and to compare radiological and clinical aspects, as well as impact of LBP on health related quality of life (QoL), depression and disability in control patients with mechanical LBP (mLBP). METHODS: Patients with RA and patients with mLBP of at least 3 months duration were consecutively recruited. All patients were examined and underwent lumbar X-ray and magnetic resonance (MR) imaging. Disc intensity, annulus fibrosis rupture, herniated nucleus pulposus (bulging, protrusion, extrusion or sequestration), stenosis, Schmorl nodes, hemangiomas, Tarlov cysts, Type I or II degeneration, ligamentum flavum hypertrophy and loss of lordosis were assessed on MR. Assessments included QoL and disability scales like RAQoL, Short Form-36, Health Assessment Questionnaire (HAQ) and Oswestry Disability Index (ODI) and depression and anxiety scales as well. RESULTS: Chronic LBP coexisted in 64.5% of patients with RA. Patients with LBP had higher scores on VAS-LBP compared to patients with RA + LBP. Additionally, patients with RA + LBP had the poorest scores on quality of life, functional disability and depression. Patients with mLBP had more frequent clinical manifestations and neurologic deficits. Patients with RA + LBP had more frequent Schmorl nodes compared to patients with mLBP. CONCLUSION: The association of RA with LBP leads to a significant decrease in the functional capacity and QoL as well as increase in depression risk. Appropriate diagnostic procedures and treatments should be administered to avoid further deterioration in functional disability and QoL.
Keywords: Rheumatoid arthritis; low back pain; quality of life; magnetic resonance; disability